The Role and Awareness of Food Rescue NGOs in Hungary: Based on the Results of an Online Survey - Veronika Keller; Péter Huszka (Chemical Engineering Transactions)
The issue of food waste is a significant global challenge that is closely linked to the United Nations Sustainable Development Goals (SDGs). Non-governmental organisations (NGOs) are of critical importance in addressing this issue, spearheading initiatives aimed at curbing overproduction and waste. This study introduces the principal non-governmental organisations (NGOs) engaged in food waste reduction and assesses the extent of public awareness of their activities in Hungary. The research is based on secondary data and an online survey of 231 respondents. It explores initiatives such as shopping communities, the Hungarian Food Bank Association, the No Leftovers program, and the Munch app. The findings indicate that food rescue organisations are not widely recognised, which constrains their potential impact. However, younger generations demonstrate greater engagement with digital food-saving solutions. The lack of public awareness underscores the necessity for enhanced marketing and educational initiatives. Furthermore, the study identifies a generational and socio-economic divide, with younger, higher-income individuals demonstrating a greater commitment to sustainable practices. The study offers insights into how NGOs can enhance their impact through the strategic use of technology and targeted communication.